Race-ing antitrust - Capers, Bennett; Day, Gregory (Michigan law review, 2023)
Antitrust law has a race problem. To spot an antitrust violation, courts inquire into whether an act has degraded consumer welfare. Since anti-competitive practices are often assumed to enhance consumer welfare, antitrust offenses are rarely found. Key to this framework is that antitrust treats all consumers monolithically; that consumers are differently situated, especially along lines of race, simply is ignored. We argue that antitrust law must disaggregate the term "consumer" to include those who disproportionately suffer from anticompetitive practices via a community welfare standard. As a starting point, we demonstrate that anti-competitive conduct has specifically been used as a tool of oppression while, at other times, minorities are the unintended victims of anti-competitive practices. In turn, this article leans on Critical Race Theory (CRT) to explore ways that antitrust's "colorblind" stance has failed communities of color. We also explain why antitrust law is an ideal regime to address systemic racism. Consider that antitrust law is concerned with structures; just as enforcement scrutinizes whether conduct has made a market more or less likely to promote consumer welfare, antitrust should scrutinize whether anti-competitive conduct has made a market more or less likely to benefit all consumers. To put it another way, antitrust's claimed purpose is to enhance consumer welfare by maximizing allocative efficiency, but it ignores how discrimination is similarly inefficient if resources are misallocated along race lines rather than their most productive uses. Finally, by embracing the intellectual backbone of antitrust law as well as CRT's lessons about power structures, we make the case that antitrust's goal should be reimagined to benefit not only the welfare of all consumers but the welfare of communities as well.